Sex difference in heart failure risk associated with febuxostat and allopurinol in gout patients - Cheng, Ching-Lan; Yen, Chi-Tai; Su, Chien-Chou; Lee, Cheng-Han; Huang, Chien-Huei; Yang, Yea-Huei Kao (Frontiers in Cardiovascular Medicine, 2022)
Background: Gout or rapid reduction in serum uric acid level may increase the incidence of heart failure (HF). To compare the risk of HF between febuxostat and allopurinol in gout patients with coexisting CV diseases, the various severity would likely to confound the risk estimation. Gout and HF are both sex-related diseases, and the risk difference from the urate lowering agents between female and male remains unknown. Aims: To evaluate the HF hospitalisations risk of febuxostat and allopurinol in gout patients in the real-world settings. Methods: A population-based cohort enrolled patients with allopurinol or febuxostat initiation during 2011 to 2018. Participants were grouped into, without (low CV risk group) or with history (high CV risk group) of recent major CV admission. The primary outcome was HF hospitalisation. The secondary outcomes were composite CV events, all-cause mortality, and cause of CV mortality. We used the ‘as-treated’ analysis and Cox proportional hazards model after propensity score (PS) matching. Patients were further stratified into male or female to evaluate the gender differences. Results: Febuxostat users had a significantly higher risk of HF hospitalisation than allopurinol users in gout patients either with low CV risk (hazard ratio [HR] 1.39; 95% confidence interval [CI] 1.25-1.55) or high CV risk (HR 1.36; 95% CI 1.22-1.52). Particularly, women with gout had a higher risk of HF hospitalisation than men. Conclusions: The HF hospitalisation risk was highest in gout women with high CV risk and febuxostat use. Monitoring of HF is warranted in these patients.